RELATIONSHIP OF AGING AND DEPRESSION LEVEL OF OLDER PEOPLE IN BANTEN: A COMPARISON STUDY - Lani Natalia Watania; Yakobus Siswadi (Universitas Pelita Harapan, 2019)
Population of elderly worldwide is growing rapidly include ing in Indonesia. This triggers increased health issues such as depression. But, the literature is lacking on more evidence on age as the risk factors of elderly depression. Hence the study aimed to investigate age as one of the risk factors for elderly depression. The purpose of this study was to compare depression levels between two life-stage subgroups: young-old (65-74 years old) and old-old (75-84 years old) group at nursing home in Banten area. This was a quantitative study with comparative cross-sectional design, which included a total of 40 elderly respondents. Data was analyzed using Mann-Whitney U test The study results showed that there was no significant difference on depression level between the two life-stage subgroups (p-value= 0.381).One possible factors which effected the study results may be protective factors such as family supports, socioeconomics status, engeagement in social activities and religious or spiritula involvement. The further research needed to explore more on the risk factors and protective factors related to elderly depression.